A Scoring Model to Evaluate Offshore Oil Projects. Issue 3 (3rd July 2022) - Giadedi, Abdulhakim; Daim, Tugrul U.
Abstract: Offshore oil projects are defined as mega projects that are associated with larger project size, higher complexities with inherent risks, and higher chances of failure in the investment and decision-making processes. These characteristics require significant assessment and acquisition methods in order to reduce failure. Financial analysis is the most widely used method to evaluate offshore oil projects; however, there are several other internal and external factors that affect the overall success of offshore oil projects. A comprehensive approach and advanced tools are required to evaluate factors that can have a significant impact before any investment decisions are made. This paper evaluates the important factors that influence offshore oil project investment decisions as well as score their weight of impact using a multi criteria decision model. A comprehensive literature review was conducted to recognize the complexities of these factors. Four perspectives were identified in order to assess the attributes that are necessary for successful offshore projects. These perspectives are economical, technical, political and environmental and safety. A hierarchical decision model (HDM), along with desirability curves, was implemented to evaluate offshore oil projects in order to improve investment decisions and reduce failure.